Polyolefin‐Magnesium Interactions Performing Powder Injection Molding Process. Issue 11 (6th August 2018) - Schaper, Johannes G.; Scharnagl, Nico; Wolff, Martin; Ebel, Thomas; Neumann, Silvio; Willumeit‐Römer, Regine
Abstract : The introduction of magnesium into the metal injection molding (MIM) process has shown that sintering results are drastically influenced by the selection of the backbone polymer of the binder system. The polymer is needed to ensure the shape stability after injection molding until the sintering process begins. Using polyethylene (PE) based polymers result in a strong sintering inhibiting effect while polypropylene (PP) based polymers do not show such a negative influence on the sintering of the magnesium powder. This work displays a systematic investigation why these two polyolefins show such a strong difference when used as backbone polymers for MIM of magnesium. According to the literature, PE decomposes mainly into 1‐alkenes and n‐alkanes while PP decomposes into branched iso‐alkenes and iso‐alkanes. The different thermal decomposition products of PE react with magnesium forming metastable carbides that decompose into carbon. Carbon can act as a barrier between neighboring powder particles inhibiting the sintering process. The decomposition products of PP do not react in the same extent leading to the fact that sintering is still possible. The negative effect of the carbon can be reversed when hydrogen is used as a sintering atmosphere resulting in improved sintering even when PE is used. Abstract : Within this work, fundamental differences in the debinding behavior between PE‐ and PP‐based binders in the Mg‐MIM process leading to completely different sintering activity is detected and understood. PE in contrast to PP shows a strong sintering inhibiting effect because its thermal decomposition products forming metastable Mg carbides that decompose into carbon acting as sintering barrier between Mg powder particles.